Multimodal Discourses of Moral Values in the Bahasa Indonesia Kawan Seiring Textbook for Grade 3 Primary Schools: A Critical Appraisal Study - Andi Sahtiani Jahrir; Muhammad Tahir (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates how moral values are represented in the Bahasa Indonesia Kawan Seiring textbook for Grade 3 primary schools, published by the Indonesian Ministry of Education, Culture, Research, and Technology (2022). Beyond its role in literacy development, the textbook functions as a curricular artefact through which children internalize moral and civic values aligned with Indonesia’s Profil Pelajar Pancasila. The study employs a qualitative multimodal critical discourse analysis (MCDA), integrating Martin and White’s (2005) Appraisal framework with Kress and van Leeuwen’s (2006) Visual Grammar. The corpus consists of eight textbook chapters containing dialogues, narratives, teacher prompts, illustrations, and reflective activities. Segments with moral orientations were identified, coded into value categories (e.g., helpfulness, politeness, tolerance, responsibility, creativity, diversity), and tabulated. Verbal texts were examined for evaluative stance (affect, judgment, appreciation), while visual texts were analyzed for ideational, interpersonal, and textual meanings. Each value was then mapped against the six dimensions of the Profil Pelajar Pancasila. Findings show that the most salient values are helpfulness, politeness, and tolerance, followed by responsibility, respect, and creativity. These values are linguistically realized through softened imperatives Apakah kamu perlu bantuanku?, affective expressions of empathy, and visually through egalitarian compositions that emphasize cooperation and inclusion. By situating morality in everyday contexts—traditional games, classroom activities, family collaboration, and digital practices—the textbook presents values as lived experiences rather than abstract doctrines. The study contributes to scholarship on textbook-mediated moral education in non-Western contexts and provides practical insights for teachers and policymakers. Kawan Seiring illustrates a hybrid pedagogy that integrates traditional norms with emerging priorities such as digital citizenship and global mindedness, positioning children as both moral agents and future global citizens.